2018
DOI: 10.1002/cyto.b.21745
|View full text |Cite
|
Sign up to set email alerts
|

CD123 expression levels in 846 acute leukemia patients based on standardized immunophenotyping

Abstract: Background While it is known that CD123 is normally strongly expressed on plasmacytoid dendritic cells and completely absent on nucleated red blood cells, detailed information regarding CD123 expression in acute leukemia is scarce and, if available, hard to compare due to different methodologies. Methods CD123 expression was evaluated using standardized EuroFlow immunophenotyping in 139 pediatric AML, 316 adult AML, 193 pediatric BCP‐ALL, 69 adult BCP‐ALL, 101 pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 30 publications
8
93
0
17
Order By: Relevance
“…Immunophenotyping was performed using standardized procedures as developed by the EuroFlow collaborative project . Whilst published information on this topic was relatively scarce and difficult to compare due to different methodologies, Bras and colleagues confirmed most observations as they extensively document in this report . Importantly, they observed that in paired B‐cell precursor ALL, CD123 expression was considerably higher at relapse than at initial diagnosis, whilst in AML, the leukemic stem cells (CD34 pos , CD38 neg fraction of tumor cells) expressed similar CD123 levels as the remainder of AML blasts.…”
Section: A Standardized Study Of Cd123 Expressionsupporting
confidence: 67%
“…Immunophenotyping was performed using standardized procedures as developed by the EuroFlow collaborative project . Whilst published information on this topic was relatively scarce and difficult to compare due to different methodologies, Bras and colleagues confirmed most observations as they extensively document in this report . Importantly, they observed that in paired B‐cell precursor ALL, CD123 expression was considerably higher at relapse than at initial diagnosis, whilst in AML, the leukemic stem cells (CD34 pos , CD38 neg fraction of tumor cells) expressed similar CD123 levels as the remainder of AML blasts.…”
Section: A Standardized Study Of Cd123 Expressionsupporting
confidence: 67%
“…With the improvements in induction therapy for pediatric B lymphoblastic leukemia, attention is gradually shifting to later time points from therapy, End of Consolidation in particular, in order to identify patients who have had inadequate response to initial therapy and who might benefit from one of multiple novel treatments now available, for example, anti-CD19 or anti-CD22 therapy. To this end, new reagents have been identified that may allow improved discrimination of hematogones from residual leukemia (17), a few of which have been demonstrated to be of potential value in defined reagent combinations tested on patient cohorts (18)(19)(20), these include CD49f (21), CD81 (22), CD123 (23), CD73 (20,24) (see Fig. 9), CD86 (20,24), and CD304 (24).…”
Section: B Lymphoblastic Leukemia/lymphomamentioning
confidence: 99%
“…The same excellent outcome for MRD negative patients is not seen in the high-risk population, emphasizing the importance of the underlying biology in interpreting the significance of MRD. In parallel, a higher sensitivity flow cytometric assay has been developed that involves the collection of larger numbers of total events with an expanded antibody panel (18,19). This assay requires more involved specimen processing and longer acquisition times with the potential for the observation of new artifacts.…”
Section: B Lymphoblastic Leukemia/lymphomamentioning
confidence: 99%
“…По мере дифференцировки клетки-предшественницы экспрессия α-цепи рецептора к ИЛ-3 увеличивается на клетках миелоидного ростка и сохраняется до поздних стадий созревания [30]. Низкая экспрессия сохраняется на гранулоцитах, несколько выше она бывает на эозинофилах и моноцитах [30]. Базофилы и плазмоцитоидные дендритные клетки (ПДК) характеризуются наиболее высокой экспрессией CD123.…”
Section: экспрессия α-цепи рецептора ил-3 на нормальных клеточных попunclassified
“…Базофилы и плазмоцитоидные дендритные клетки (ПДК) характеризуются наиболее высокой экспрессией CD123. Мембранная экспрессия рецептора на ПДК отличается самыми высокими значениями интенсивности флюоресценции, отражающей плотность экспрессии рецептора при иммунофенотипическом исследовании [30].…”
Section: экспрессия α-цепи рецептора ил-3 на нормальных клеточных попunclassified